Changes in joint kinetics during learning the longswing on high bar - Williams, G. K. R.; Irwin, G.; Kerwin, D. G.; Newell, K. M. (Journal of Sports Sciences, 2015)
Biomechanics helps us understand the association between technique changes and performance improvement during learning. The aim of this research was to investigate joint kinetic characteristics of technique during learning of the longswing on the high bar. Twelve male, novice participants took part in the learning study. During swing attempts in 8 weekly testing sessions, kinematic data were collected. Inverse dynamics analysis was performed from known zero forces at the toes to quantify joint moments and power at the hips and shoulders. Key biomechanical constraints that limited performance outcome were identified based on changes in joint kinetics during learning. These constraints were the ability to perform a large shoulder power and to overcome passive kinetics acting during the downswing. Constraints to action at the level of joint kinetics differentially challenge learners and therefore could underpin more individual, specific learning interventions. Functional phases, defined by maximum hyperextension to flexion of the hips and maximum flexion to extension of the shoulders, did not describe the key joint kinetics of the hip and shoulder for novices. The functional phases may serve however to identify novices that were unable to overcome the passive kinetic constraint.